Autoimmune episodic ataxia in patients with anti-CASPR2 antibody-associated encephalitis. Issue 4 (July 2017) - Joubert, Bastien; Gobert, Florent; Thomas, Laure; Saint-Martin, Margaux; Desestret, Virginie; Convers, Philippe; Rogemond, Véronique; Picard, Géraldine; Ducray, François; Psimaras, Dimitri; Antoine, Jean-Christophe; Delattre, Jean-Yves; et al.
Abstract : Objective: To report paroxysmal episodes of cerebellar ataxia in a patient with anti–contactin-associated protein-like 2 (CASPR2) antibody-related autoimmune encephalitis and to search for similar paroxysmal ataxia in a cohort of patients with anti–CASPR2 antibody-associated autoimmune encephalitis. Methods: We report a patient with paroxysmal episodes of cerebellar ataxia observed during autoimmune encephalitis with anti-CASPR2 antibodies. In addition, clinical analysis was performed in a retrospective cohort of 37 patients with anti-CASPR2 antibodies to search for transient episodes of ataxia. Paroxysmal symptoms were further specified from the referral physicians, the patients, or their relatives. Results: A 61-year-old man with limbic encephalitis and anti-CASPR2 antibodies developed stereotyped paroxysmal episodes of cerebellar ataxia, including gait imbalance, dysarthria, and dysmetria, 1 month after the onset of the encephalitis. The ataxic episodes were specifically triggered by orthostatism and emotions. Both limbic symptoms and transient ataxic episodes resolved after treatment with steroids and IV cyclophosphamide. Among 37 other patients with anti-CASPR2 antibodies, we identified 5 additional cases with similar paroxysmal ataxic episodes that included gait imbalance (5 cases), slurred speech (3 cases), limb dysmetria (3 cases), and nystagmus (1 case). All had concomitant limbic encephalitis. Paroxysmal ataxia was not observed in patients with neuromyotonia or Morvan syndrome. Triggering factors (orthostatism or anger) were reported in 4 patients. Episodes resolved with immunomodulatory treatments in 4 patients and spontaneously in 1 case. Conclusions: Paroxysmal cerebellar ataxia must be added to the spectrum of the anti-CASPR2 antibody syndrome.